Diesel, petrol or electric vehicles: What choices to improve urban air quality in the Ile-de-France region? A simulation platform and case study. (15th November 2020) - Andre, M.; Sartelet, K.; Moukhtar, S.; Andre, J.M.; Redaelli, M.
Abstract: Air pollution from road traffic and its mitigation is a major concern in most cities. A platform for simulating pollutant emissions and concentrations was developed and applied to the Île-de-France Region (Greater Paris) of France, taking account of anthropogenic and natural sources and 'imported' pollution from elsewhere in France and Europe. Four technological scenarios for 2025 were studied and compared to the 2014 reference situation (1-REF). These scenarios included the current evolution of the park with widespread adoption of diesel particulate filters (DPFs) (2-BAU), decline in the sale of diesel vehicles and a corresponding increase in petrol vehicle sales (3-PET), promotion of electric vehicles in urban areas (4-ELEC), and a combinaison with a decrease in traffic of about 15% in the densely populated area inside the A86 outer ring road (5-AIR). The corresponding vehicle fleets were determined using a fleet simulation model. Traffic pollutant emissions were computed with the COPERT4 European methodology and hourly traffic data over the Île-de-France road network. Particulate matter (PM10, PM2, 5 and PM1, 0 ), particles number (PN), black carbon (BC), organic matter (OM), nitrogen oxides (NOx) and nitrogen dioxide (NO2 ), non-methane volatile organic compounds (VOC), ammonia (NH3 ), carbon monoxide (CO) and carbon dioxide (CO2 ) were considered. Emissions for other sectors were taken from a regional inventory. Emissions outside the Île-de-France region (Europe and France) were derived from the European and French emission inventories. Pollutant concentrations (PM2, 5, PM10, organic and inorganic PM10, PN, BC, NO2 and O3 ) were simulated over nested domains (Europe, France and Île-de-France) using the Polyphemus platform for two scenarios (2-BAU and 3-PET). Methodological aspects and results for Île-de-France are discussed here. All scenarios led to a sharp decrease in traffic emissions in Île-de-France (−30% to −60%) by 2025. The decline in diesel induced a stronger renewal of the fleet. PM and NOx emissions were more strongly reduced than VOC or NH3 . Traffic reduction reduced all emissions in the densely populated area within the A86 outer ring road (−20% to −45% for exhaust particles and gaseous pollutants). The 2-BAU and 3-PET scenarios lowered annual average concentrations, especially for NO2 and BC, and more strongly influenced daily-peak than daily-average concentrations. In Île-de-France, PM of diameter <10 μm (PM10 ), and NO2 concentrations, decreased in the most densely populated areas. The entire population would benefit from a PM10 annual mean concentration decrease of ≥0.4 μg/m 3, and the annual mean NO2 concentration would decrease by ≥ 10 μg/m 3 for 40–50% of the population. For other pollutants (PM2.5, secondary pollutants, etc.), reductions were more limited, due to the other activity sectors and atmospheric chemistry. Ozone concentrations might even increase in urban locations, suggesting an increase in oxidants and thus an increase in secondary aerosol formation if precursors were not reduced. Differences between 2-BAU and 3-PET scenarios were slight. For PM and NO2 concentrations, the petrol scenario was slightly more favorable than the "business-as-usual" scenario with diesel vehicles and DPF; differences were strong for primary particles and NO2 and weak for secondary compounds. This slight advantage was due to lower emissions and accelerated fleet renewal (higher proportion of Euro 5 & 6). Highlights: Pollutants emissions and concentrations simulated for vehicle technology scenarios. By 2025, a decrease of traffic emissions by −30 to −60% in Île-de-France. Decrease of average levels and of high concentrations occurrences. Slight advantage to a Petrol scenario by lower emissions and fleet renewal. Electric vehicles and Traffic reduction in dense area would increase the benefits.